The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1039/d0ee03898a
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-long-life and highly reversible Zn metal anodes enabled by a desolvation and deanionization interface layer

Abstract: Zinc metal anode in aqueous zinc-ion batteries (AZIBs) is considerably impeded by uncontrollable dendrite growth and intricately water-induced corrosion, leading to low Coulombic efficiency (CE) and limited lifespan. Herein, a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
207
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(226 citation statements)
references
References 52 publications
2
207
0
Order By: Relevance
“…[ 58–61 ] And the negative surface charges can lead to the closely adhesion between zinc anode and CG separator under the electrostatic attraction and strong binding energy between O groups and zinc anode (OH/Zn: −7.64 eV, O/Zn: −26.33 eV), [ 62 ] which greatly shortens the path of Zn 2+ ions transmission and constructs a special separator–anode interface. [ 62,63 ] Additionally, the negative charged CG separator surface can effectively deanion (SO 4 2– ) via the electrostatic repulsion, [ 64 ] thus suppressing the formation of side effects (Zn 4 SO 4 (OH) 6 ·5H 2 O), which is demonstrated in Figure S7d, Supporting Information. Furthermore, the electrochemical impedance spectrum (EIS) proves that the fast ion diffusion and quick charge transfer process can be achieved by CG separator (Figure 3d).…”
Section: Resultsmentioning
confidence: 99%
“…[ 58–61 ] And the negative surface charges can lead to the closely adhesion between zinc anode and CG separator under the electrostatic attraction and strong binding energy between O groups and zinc anode (OH/Zn: −7.64 eV, O/Zn: −26.33 eV), [ 62 ] which greatly shortens the path of Zn 2+ ions transmission and constructs a special separator–anode interface. [ 62,63 ] Additionally, the negative charged CG separator surface can effectively deanion (SO 4 2– ) via the electrostatic repulsion, [ 64 ] thus suppressing the formation of side effects (Zn 4 SO 4 (OH) 6 ·5H 2 O), which is demonstrated in Figure S7d, Supporting Information. Furthermore, the electrochemical impedance spectrum (EIS) proves that the fast ion diffusion and quick charge transfer process can be achieved by CG separator (Figure 3d).…”
Section: Resultsmentioning
confidence: 99%
“…The work demonstrated that the CNC–graphene interface layer with negative surface charges could simultaneously generate a deanionization shock by spreading cations but screening anions to obtain redirected Zn deposition parallel to the (0002) Zn plane. [ 38 ] To sum up, the development of nanocellulose for EES has received wide attention due to the advantages of its intrinsic properties and structures, as demonstrated in Figure 4.…”
Section: Preparation and Properties Of Nanocellulosementioning
confidence: 99%
“…Zn anode surface modifications (such as ZrO 2 and graphene) can guide the even charge distribution and contribute to the controllable nucleation sites for Zn 2+ , which significantly suppressed dendrites growth in repeated cycling. [17,[24][25][26][27] The electrolyte-based approaches positively influence the performance of Zn anode by forming an artificial solid electrolyte interface on Zn anode surface or decreasing the activeness of H 2 O in the electrolyte, leading to the dendrite-free anode. [28][29][30][31] However, these two methods usually increase the internal impedance or polarization.…”
Section: Introductionmentioning
confidence: 99%